Quality assessment of robotic repair of benign ureteral strictures: A Canadian, single-center experience - Luke, William; Jain, Archit; Lim, Christina; Rotz, Heather; Myers , Zoe; Lahiji, Reza; Luke, Patrick P.W. (Canadian Urological Association Journal, 2025)
INTRODUCTION: Endourologic treatments are first-line interventions for short ureteral strictures. With long strictures and endourologic failures, open repair has historically been used; however, robotic-assisted approaches have recently been shown to be effective. As a quality measure, we wanted to assess the performance of robotic ureteral reconstruction compared with open surgical repair during our transition to robotic surgery at a Canadian tertiary care center. METHODS: From 2011-2024, 43 complex ureteral stricture cases (19 open, 24 robotic) were performed. The primary outcome was six-month success defined by a composite of stent/pain-free status and renogram elimination half-life (T½). Secondary outcomes included length of stay, operative time, estimated blood loss, and complications. RESULTS: Success rates at six months were non-significantly different between robotic and open repair (83% vs. 79%, p=0.36). Length of stay was shorter in the robotic group (3.1±1.9 vs. 4.9±3.3 days, p=0.018). Estimated blood loss (231±84 vs. 244±170 mL, p=0.30) and operative time (220±67 vs. 214±74 minutes, p=0.40) were comparable between groups. Complication rates were similar between groups. CONCLUSIONS: Overall, robotic reconstruction yields equivalent six-month success to open repair, with shorter length of stay. These findings support continuing robotic-assisted ureteral reconstruction as a safe and effective alternative to open surgery, offering equivalent short-term success and reduced hospital stay.